Effect of Raloxifene on Periapical Lesions in Ovariectomized Rats - Gomes-Filho, Joao Eduardo [UNESP]; Wayama, Marcelo Tadahiro [UNESP]; Menegati Dornelles, Rita Cassia [UNESP]; Ervolino, Edilson [UNESP]; Coclete, Gilberto Aparecido [UNESP]; Tobias Duarte, Paulo Carvalho [UNESP]; Yamanri, Guilherme Hiroshi [UNESP]; Lodi, Carolina Simonetti [UNESP]; Dezan-Junior, Eloi [UNESP]; Angelo Cintra, Luciano Tavares [UNESP] (Elsevier B.V., 2015)
Introduction: The aim of this study was to evaluate the effect of raloxifene (RLX) during progression of periapical lesions in ovariectomized (OVX) rats. Methods: Female Wistar rats were OVX or subjected to sham surgery and received vehicle or MX by gavage for 90 days. The treatment groups were as follows: sham surgery and treated with vehicle (SHAM-veh), OVX and treated with vehicle (OVX-veh), and OVX and treated with RLX (OVX-RLX). During treatment, the pulp of lower first molar was exposed to the oral. environment for induction of periapical lesion that was analyzed 7 or 30 days aftdr procedure. Blood samples were taken from jugular vein for measurement of estradiol, and the mandibles were removed and prepared for radiographic, histopathologic, histometric, and immunohistochemical analysis. Results: Estradiol plasma concentration showed hypoestrogenism in OVX rats. The histopathologic analysis of the OVX/RLX group was similar to that of the SHAM-veh group, whereas OVX-veh group showed larger penapical lesions with more intense inflammatory response and more cells positive for tartrate-resistant acid phosphatase. Radiographically, the groups were similar, but lesions on day 7 were smaller than lesions on day 30. Conclusions: The results suggest that hypoestrogenism potentiates the progression of periapical lesions, and such condition was reversed by treatment with RLX.
Keywords: Bone metabolism; estrogen; ovariectomized; periapical lesion; raloxifene